Water Quality Status of Raja Ampat Island Natural Marine ReserveBased on the Seawater Physical Parameters - Simon Patty; Marenda Pandu Rizqi; Rikardo Huwae; Ferdimon Kainama (Sam Ratulangi University, 2020)
Observation of water quality in Raja Ampat Islands Natural Water Reserve (SAP Kepulauan Raja Ampat), was carried out in August-September 2019. This study aims to determine the water quality and the pollutionâ€™s status based on the water physical parameters. Measurement of all parameters was conducted in-situ using the EXO-2 device, while the water clarity was measured with a Secchi disk. The results of statistical analysis using the T-Test showed that the TDS content in the surface layer compared to the bottom was significantly different. Pollution index calculation results show that the waters of the Raja Ampat Islands are still in good condition (not polluted). Variations in temperature, salinity, brightness/clarity, turbidity, conductivity (DHL) and the dissolved solids values (TDS) are still adequate for the well-being of coral reefs and various marine biota inhabited the waters.Keywords: Water quality, physical characteristics, Raja AmpatÂ ABSTRAKPengamatan kualitas air di SAP Kepulauan Raja Ampat, telah dilaksanakan pada bulan Agustus-September 2019. Penelitian ini bertujuan untuk mengetahui kualitas perairan dan menentukan status pencemaran berdasarkan parameter fisika air laut. Pengukuran semua parameter dilakukan secara in situ (langsung di lapangan) dengan menggunakan alat EXO-2, kecuali kecerahan air laut diukur dengan cakram sechi (sechi disk). Hasil analisis statistik dengan menggunakan uji-t menunjukkan bahwa kandungan TDS di lapisan permukaan dengan dekat dasar adalah berbeda nyata. Hasil perhitungan indeks pencemaran menunjukkan perairan Kepulauan Raja Ampat masih dalam kondisi baik (tidak tercemar). Variasi nilai suhu, salinitas, kecerahan, kekeruhan, konduktivitas (DHL) dan jumlah zat padat terlarut (TDS) masih baik untuk kehidupan dan perkembangan terumbu karang serta berbagai biota laut yang hidup didalamnya.Kata kunci: Kualitas air, karakteristik fisika, Raja Ampat